2020
DOI: 10.1136/bmjopen-2018-028593
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific prevalence and influencing factors of osteopenia and osteoporosis in Chinese rural population: the Henan Rural Cohort Study

Abstract: ObjectiveThe aims of this study were to describe distributions of the prevalence of osteopenia and osteoporosis and identify the potential risk factors by gender in a Chinese rural population.DesignA cross-sectional survey.Setting and participantsA total of 8475 participants (18–79 years) were obtained from the Henan Rural Cohort Study. Bone mineral density (BMD) of the calcaneus for each individual was measured by ultrasonic bone density apparatus. Logistic regression models were used to evaluate associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…We did, however, observe that the change in the amount of time spent in prolonged sedentary bouts (20 to 30 min and >60 min) over a 24-month time period was inversely associated with lumbar spine BMD in older women independent of changes in MVPA levels. Thus, our results point to the importance of encouraging older women who are most affected by bone diseases (osteopenia and osteoporosis) compared to men [28,29] to reduce prolonged time spent in sedentary behavior such that sedentary bouts do not exceed periods longer than 20 min without an interruption, as this may result in beneficial changes in BMD.…”
Section: Discussionmentioning
confidence: 71%
“…We did, however, observe that the change in the amount of time spent in prolonged sedentary bouts (20 to 30 min and >60 min) over a 24-month time period was inversely associated with lumbar spine BMD in older women independent of changes in MVPA levels. Thus, our results point to the importance of encouraging older women who are most affected by bone diseases (osteopenia and osteoporosis) compared to men [28,29] to reduce prolonged time spent in sedentary behavior such that sedentary bouts do not exceed periods longer than 20 min without an interruption, as this may result in beneficial changes in BMD.…”
Section: Discussionmentioning
confidence: 71%
“…Data from seven Asian countries revealed that the prevalence of osteoporosis can vary from 41% to 90% among men and women, depending on region and age [28][29][30][31]. A study conducted among 8475 Chinese subjects found that half of the population had moderate to severe osteoporosis levels and concluded that the prevalence of osteoporosis in women was higher than in men [32]. A meta-analysis also supports that there is an association between female gender and osteoporosis [33].…”
Section: Discussionmentioning
confidence: 99%
“…2 Due to the progressive aging trend of the population, the morbidity and mortality of OP and associated fractures grows year by year, 3 creating an ever-increasing burden for clinical resources and economic expenses. 4,5 In the USA, the annual cost for OP-related fractures in 2005 was 17 billion dollars, with 71% of fractures occurring in women and the costs for treatment of such fractures being 75% higher than those in men, and a further 50% increase in cost to 25.3 billion dollars are projected by 2025. 6 The situation of OP in China is equally serious, as it has been predicted that the osteoporotic population will expand sharply from 83.9 million in 1997 to 212 million by 2050.…”
Section: Introductionmentioning
confidence: 99%